2021
DOI: 10.1186/s13075-021-02539-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of ultrasound-detected knee synovial abnormalities in a middle-aged and older general population—the Xiangya Osteoarthritis Study

Abstract: Background There is paucity of data on the prevalence of ultrasound-detected synovial abnormalities in the general population, and the relationship between synovial changes and knee pain remains unclear. We examined the prevalence of synovial abnormalities on ultrasound and the relationship of these features with knee pain and radiographic osteoarthritis (ROA) in a community sample. Methods Participants aged 50 years or over were from the Xiangya O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…Study participants. The Xiangya Osteoarthritis (XO) Study (discovery cohort) is a community-based longitudinal study conducted in a rural area of China (ClinicalTrials.gov identifier: NCT04033757) (13)(14)(15). Participants in the XO Study were a randomly selected sample of subjects ages 50 years or older from rural mountainous villages of Longshan County in Hunan Province, China.…”
Section: Methodsmentioning
confidence: 99%
“…Study participants. The Xiangya Osteoarthritis (XO) Study (discovery cohort) is a community-based longitudinal study conducted in a rural area of China (ClinicalTrials.gov identifier: NCT04033757) (13)(14)(15). Participants in the XO Study were a randomly selected sample of subjects ages 50 years or older from rural mountainous villages of Longshan County in Hunan Province, China.…”
Section: Methodsmentioning
confidence: 99%
“…In an original work with different ethnic Malaysian people, Chia et al reported the highest knee pain prevalence in Indian ethnic Malaysians, especially in women, than other ethnic groups [17]. In another community-based cohort study, Jiang et al evaluated chronic knee pain with MSUS and documented the highest prevalence of synovial effusion, followed by synovial hypertrophy; increased synovial abnormalities were seen associated with increased knee pain [19]. The associations between synovial hypertrophy and effusion with knee pain were more pronounced with radiographic knee OA.…”
Section: Discussionmentioning
confidence: 99%
“…[18]. Community-based cohort studies further demonstrated that US-depicted synovial hypertrophy, medial osteophytes, and synovial effusion interacted with increased knee pain risk and predicted early knee OA [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Knee pain manifests a multidimensional nature, and synovial abnormalities have been proven to be its important causes 6–9 . Ascertaining the presence of synovial abnormalities through imaging techniques at study inclusion might improve the efficacy of antiinflammation therapy on joint pain 12–15 .…”
Section: Discussionmentioning
confidence: 99%